Bibliometric Analysis of Publications in The Web of Science Database on The Subject of Public Policy (Third Sector Social Economic Review, 2025)
Public policy is the process of joint decision-making, implementation and monitoring by state and non-state actors with regard to social problems. The aim of this study is to analyse bibliometrically the articles published on public policy in the field of public administration.The research was conducted using a dataset consisting of 3,824 English-language books, articles, book chapters, conference papers, and book reviews published between 1980 and 2024 in the public administration category of the Web of Science (WOS) database. The data were bibliometrically analysed using VOSviewer software. Citation analysis, co-citation analysis, bibliographic coupling, co-authorship analysis and co-word analysis were performed. According to the results of the analysis, the country where the most articles on public policy are written is the United States of America.  Howlett was the author of the most articles. Policy Studies Journal is the journal with the highest number of articles published. The University of London ranks first among the institutions affiliated with the authors who published the most..Public policy, public administration, governance, Covid-19, policy design were found to be the most commonly used terms in public policy.
Keywords: Public Policy; Public Administration; Bibliometric Analysis; Governance; Web of Science (WoS)